Authority Of Land Deed Officers On Sale And Purchase Binding Agreements For Certificate Return Process - Riskiana, Nanda; Adjie, Habib (Devotion : Journal of Research and Community Service, 2022)
An agreement is a civil event that gives rise to rights and obligations for the parties who have agreed in the agreement. Human nature as a creature is destined to always try to maintain its existence to be sustainable. For this reason, humans will always try to fulfill their life needs without stopping for a moment. An agreement that has been agreed between the parties together, partly formed through an agreement and consciously and binding on the parties desired by those who wrote it. The agreement is a civil event contains the rights and obligations of the parties.